The Impact of Standard Gauge Railway Transport Service Quality on Customer Satisfaction: A Case of Dar Es Salaam to Dodoma route, Tanzania - Malugu , William A. (Journal of Industrial Engineering & Management Research, 2025)
This study investigated how different service quality dimensions affect customer satisfaction with Tanzania’s Standard Gauge Railway (SGR) services. Motivated by growing demand for efficient and customer-focused rail transport, the research employed a quantitative design, surveying 168 passengers using structured questionnaires. The objective was to understand how elements like assurance, reliability, tangibility, responsiveness, and empathy influence passenger satisfaction and to provide actionable insights for improving SGR operations. Descriptive statistics summarized passenger perceptions, while multiple regression analyzed the strength and significance of each service quality dimension’s impact. Results showed that assurance, reliability, and tangibility positively and significantly influenced customer satisfaction, highlighting passengers’ appreciation for skilled staff, dependable services, and a clean, modern railway environment. In contrast, responsiveness had a weak, insignificant effect, and empathy unexpectedly had a significant negative impact, indicating possible issues in how staff address individual passenger needs. Assurance and reliability emerged as the strongest predictors of satisfaction, followed by tangibility. The study recommends that management investigate the negative perception of empathy, potentially through staff training on inclusive and personalized care, and enhance responsiveness by improving complaint handling. Continuous investment in infrastructure and cleanliness is also advised to maintain and increase passenger satisfaction.